2009
DOI: 10.2151/sola.2009-020
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Air Masses over an Alaskan Glacier and Implications for Ice Core Studies in the North Pacific Region

Abstract: Simulations of 10-day backward trajectories of air masses from Mount Wrangell, an Alaskan ice core site, were calculated for 11 years on a daily basis. Results were analyzed statistically in order to interpret monthly air mass contributions over the ice core site and to discuss implications for ice core studies in the North Pacific Region (NPR).Increases in tropospheric air mass transport from EA in spring suggest favorable transport conditions for Asian dust during this season. The stratospheric air mass (< 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The bottom of the sample 96 was estimated to be 343 years old, i.e., 1665 AD (Tsushima et al, 2015). 10-day air mass 97 backward trajectory based on Lagrangian tracking method for 1992 -2002 has been already 98 reported for Alaskan regions in the troposphere (>300 hPa) (Yasunari and Yamazaki, 2009). 99…”
Section: Site Description 89mentioning
confidence: 99%
“…The bottom of the sample 96 was estimated to be 343 years old, i.e., 1665 AD (Tsushima et al, 2015). 10-day air mass 97 backward trajectory based on Lagrangian tracking method for 1992 -2002 has been already 98 reported for Alaskan regions in the troposphere (>300 hPa) (Yasunari and Yamazaki, 2009). 99…”
Section: Site Description 89mentioning
confidence: 99%
“…Thus, 138 levoglucosan/mannosan mass ratios (L/M) could be relatively high. In contrast many 139 aerosol samples showed significant concentrations of these isomers and levoglucosan 140 are reported in many aerosol samples collected from the oceans via "round-the-world Source regions could be East Asia, Eastern Russia, Siberia, higher latitudes of 182 Alaskan regions, Japan, and Canadian regions (Yasunari and Yamazaki, 2009). For 183 instance, Ivanova et al (2010) reported the frequency of heavy forest fires (e.g., borel 184 forest) in spring, summer and autumn in eastern Siberia, which is a potential source to 185…”
Section: Levoglucosan 130mentioning
confidence: 99%
“…The 63 study covers to better understand the historical atmospheric transport 64 variability between the western North Pacific region (Kawamura et al, 2012) and 65 eastern North Pacific region (this study) from source regions. Particularly, 10 day 66 backward trajectory from 1992-2002 showed that southern Alaska can receive air 67 masses from the North Pacific Regions, East Asia, Eastern Russia-Siberia, higher 68 latitudes of Alaskan regions, Japan, and Canadian regions in the troposphere (>300 69 hPa) (Yasunari and Yamazaki, 2009). Similarly, the Kamchatka Peninsula also can 70 receive air masses from Siberia, Far East, North China and Eastern Europe 2 71 (Kawamura et al, 2012).…”
Section: Introduction 38mentioning
confidence: 99%
“…[34,36,38] NOAA's HYSPLIT back trajectories corroborate published findings that a 10-day period is sufficient for air masses containing pollution from Asia to travel to the North Pacific and Alaska. [37,55] Pollution carried in these air masses could be deposited on glaciers through snow scavenging during a period of mass gain [53,56] or through permeation into supraglacial storage during a period of mass loss. [29] Supraglacial melt in the spring may introduce these recently deposited pollutants immediately into the downstream watershed throughout the range.…”
Section: Patterns Of Atmospheric Depositionmentioning
confidence: 99%
“…The use of DDT has been recorded within the last decade in China, India and DPR Korea, [31,32] with atmospheric transport across the Pacific [19,33,34] and preferential OCP snow scavenging [13,35] increasing the likelihood of deposition onto Alaskan glaciers. [36][37][38] Recently retrieved ice core records from Interior Alaska indicate that the strengthening Aleutian low has resulted in increased snow deposition in the Alaska Range since 1840. [39] This increase of precipitation may allow for the greater success of OCP atmospheric scavenging and glacial deposition.…”
Section: Introductionmentioning
confidence: 99%